PENGARUH PENILAIAN KINERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI PIZZA HUT AHMAD YANI PADANG - Aminar Surtra Dewi; David David (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to prove and analyze the effect of performance appraisal and work discipline on job satisfaction of employees of Pizza Hut Ahmad Yani Padang Branch, either individually or collectively. In this study, 45 employees were used using the census method. The data used is primary data. The data collection process was carried out through direct observation by distributing questionnaires to respondents. The data analysis method used in this research is multiple regression and t-statistical testing and F-statistical test. The data processing is done by using the SPSS program. Based on the results of hypothesis testing, it was found that performance appraisal had a significant effect on employee work discipline, the same thing was found in the work discipline variable that had a significant effect on the performance of Pizza Hut employees, Ahmad Yani Padang Branch, besides that performance appraisal and discipline together had a significant effect on job satisfaction. employees of Pizza Hut Branch Ahmad Yani Padang